(untitled) (Anclajes, 2026)
Foucault’s notion of the disciplinary society and its deployment in the realm of narrative reveal the ‘panoptic city’ in the realist novel and then in the contemporary novel, which emerges from shifts in modern society. Los Cachorros (1967) by Mario Vargas Llosa is a key example of how mechanisms of social discipline are perfected, by which the subjects who begin their ‘learning’ process not only transform into docile bodies, but also adopt the imaginary apparatus of power as an extension of their own being.